2018
DOI: 10.1007/s12524-017-0738-y
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Mapping of Soil Organic Carbon Using Regression Kriging and Remote Sensing

Abstract: Geo-spatial mapping of soil organic carbon using regression kriging was performed for Lalo khala sub-watershed (a part of Solani watershed) located in western Uttar Pradesh, India. Soil organic carbon was predicted using eight predictor variables derived from the advanced space borne thermal emission and reflection radiometer satellite images and digital elevation model. The soil organic carbon was determined in 248 soil samples collected randomly within a 300 m 2 grid overlaid on the study area. Out of the ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
1
5
0
3
Order By: Relevance
“…This finding coincided with Pei et al [29], in the case of using the single flow direction algorithm method to calculate TWI, like in our research. Our results are in agreement with Kumar et al [81] who reported that the correlation between TWI and SOC in a tropical region (India) was 7%. She et al [82] also stated that TWI is positively correlated with SOC content.…”
Section: The Impact Of Environmental Variables On Soc Tn and Soil Phsupporting
confidence: 93%
“…This finding coincided with Pei et al [29], in the case of using the single flow direction algorithm method to calculate TWI, like in our research. Our results are in agreement with Kumar et al [81] who reported that the correlation between TWI and SOC in a tropical region (India) was 7%. She et al [82] also stated that TWI is positively correlated with SOC content.…”
Section: The Impact Of Environmental Variables On Soc Tn and Soil Phsupporting
confidence: 93%
“…La comunidad científica ha desarrollado mapas y bases de datos regionales, continentales y mundiales, que sirven de base para la evaluación del riesgo del suelo; no obstante, algunos productos cartográficos derivados de levantamientos de suelos y generados mediante técnicas de mapeo convencionales, son de escala pequeña y carecen de detalles en los límites espaciales (Arrouays et al 2017). Dado esto, el mapeo digital de suelos (MDS), definido por Lagacherie y McBratney (2006), emerge como una herramienta de conocimiento útil para analizar patrones espaciales de las propiedades del suelo en función de datos auxiliares disponibles, relacionados con clima, vegetación, topografía, material parental y uso del suelo (Hinge et al 2018;Kumar et al 2018).…”
unclassified
“…VV polarization is mainly directly affected by the ground and canopy, whereas VH includes stem-ground double scattering and volume scattering [69] that has more interference information, so VV_5 is more important than VH_5 in orchard. The results in Figure 6a also indicate that CI and BI2 have made great contributions in orchard, due to soil color and soil brightness index having a high correlation with SOC content [19,70,71]. For dry land, BI2 also has a great influence on the prediction accuracy of SOC (Figure 6b).…”
Section: Variable Importancementioning
confidence: 82%